The Educational Position and Status of Albanians in Kosovo (1941-1960) - Rahimi, Sefedin (Journal of History Culture and Art Research, 2022)
Kosovo and other Albanian regions in the Serbian, Croatian, and Slovenian Kingdoms, and later Yugoslavia, had a more difficult position and status than during the Ottoman Empire's many centuries of rule; they did not have an equal status and position to other people and nationalities who lived on Yugoslavia's territory. The political, economic, and social conditions were extremely difficult, and education was not discussed at all because the Yugoslav occupiers, particularly the Serbian occupiers, who played a dominant role, did not allow Albanians and other ethnic groups to be educated in their native language, but only in Serbo-Croatian. As a result, this paper will examine the educational and developmental status of Albanians during WWII and thereafter until 1950s, in order to assess the educational situation of Albanians during this time period, comparing the educational circumstances of both the occupiers and rulers in Kosovo, the fascists and the SFR of Yugoslavia, who targeted the Albanian people of Kosovo.